The effect of different root canal irrigants on the sealing ability of Bioceramic sealer. (Mustansiria Dental Journal, 2018)
The aim of this study was to investigate the effect of different irrigants (EDTA,MTAD, CHX) on the sealing ability of new Bioceramic root canal sealer. Materialand methods: A total of sixty extracted human single-rooted premolar teeth wereused. After instrumentation, teeth were randomly divided into three main groups(n=20) according to the type of final irrigants used. In group (A) 17% EDTA wasused. Group (B) irrigants was MTAD. In group (C) irrigant was 2% CHX. Each maingroup further subdivided into two subgroup (n=10) according to the type of sealerused. Subgroup (1) canals obturated with Bioceramic sealer. In subgroup (2) canalsobturated with AH plus sealer. After incubation period for one week the roots wereplaced in 2% methylene blue dye and kept in incubator for 48 hours then the rootswere cleared, dye penetration measured by stereomicroscopic. Results: statisticalsignificant difference was found between groups (p